2021
DOI: 10.25518/2295-8010.1948
|View full text |Cite
|
Sign up to set email alerts
|

Diversité piscicole et paramètres démographiques des principales espèces de poisson du réservoir de Samandeni, Burkina Faso

Abstract: La gestion de la pêcherie du réservoir de Samandeni au Burkina Faso, nouvellement mise en eau en 2017 nécessite des informations fiables qui sont pour l’instant éparses, insuffisantes voire inexistantes. Ce travail vise à combler ce gap à travers une analyse de la diversité, des paramètres de croissance et d’exploitabilité de la faune piscicole de ce réservoir. Pour ce faire, les poissons ont été échantillonnés au filet maillant et épervier entre avril 2018 et janvier 2019. Les espèces ont été identifiées et c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
1
5
2
Order By: Relevance
“…We noted that the estimated Z-value in the present study was much larger than those of [21] in lakes Doukon and Togbadji, Benin (Z = 2.21 yrs −1 ) and [22] in the Golinga and Bontanga reservoirs in northern Ghana (2.64 and 2.03 yrs −1 ). On the contrary, mortality in this study remains comparatively lower than that obtained by [6] in the same reservoir and for the same species before its opening to fishing. In this study, the value of natural mortality (M) was recorded at 1.36 yrs −1 , resulting in an instantaneous fishing mortality coefficient (F) of 1.68 yrs −1 .…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…We noted that the estimated Z-value in the present study was much larger than those of [21] in lakes Doukon and Togbadji, Benin (Z = 2.21 yrs −1 ) and [22] in the Golinga and Bontanga reservoirs in northern Ghana (2.64 and 2.03 yrs −1 ). On the contrary, mortality in this study remains comparatively lower than that obtained by [6] in the same reservoir and for the same species before its opening to fishing. In this study, the value of natural mortality (M) was recorded at 1.36 yrs −1 , resulting in an instantaneous fishing mortality coefficient (F) of 1.68 yrs −1 .…”
Section: Discussioncontrasting
confidence: 89%
“…A comparative analysis of the fish population parameter estimates for different settings is provided in 2 and Table 3), the asymptotic length values reported in the present study were found to be comparatively higher than those obtained by [21] in two lakes in Benin and [22] in the Botanga reservoirs, Tono and Golinga in northern Ghana. Similarly, the present study reported higher growth constants than [6] and [8]. On the contrary, the asymptotic length estimated in the present study was lower than the estimates documented by other studies such as [6] and [8].…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations